Maternal hypothalamus-pituitary-adrenal (HPA) system activity and stress during pregnancy: Effects on gestational age and infant's anthropometric measures at birth. (August 2018) - Gilles, Maria; Otto, Henrike; Wolf, Isabell A.C.; Scharnholz, Barbara; Peus, Verena; Schredl, Michael; Sütterlin, Marc W.; Witt, Stephanie H.; Rietschel, Marcella; Laucht, Manfred; Deuschle, Michael
Highlights: Moderate maternal prenatal distress is associated with fetal development leading to a reduction of anthropometric measures at birth. Modest, but significant associations between maternal prenatal distress and altered diurnal cortisol patterns were observed. A flattened cortisol decline across the day and higher evening cortisol were significantly associated with reduced length of gestation. Minor changes in maternal cortisol concentrations may play a crucial role in transmitting prenatal early life stress to the fetus. Our results highlight the importance of early recognition of moderate prenatal distress: women at risk may benefit from early interventions. Abstract: Background: Prenatal maternal stress might be a risk for the developing fetus and may have long-lasting effects on child and adult vulnerability to somatic and psychiatric disease. Over-exposure of the unborn to excess glucocorticoids and subsequent alteration of fetal development is hypothesized to be one of the key mechanisms linking prenatal stress with negative child outcome. Methods: In this prospective longitudinal study, mothers-to-be (n = 405) in late pregnancy (36.8 ± 1.9 weeks of gestational age) and their singleton neonates were studied. We investigated the impact of different prenatal stress indices derived from six stress variables (perceived stress, specific prenatal worries, negative life events, symptoms of depression, trait anxiety, neuroticism) and diurnal maternal saliva cortisol secretion on gestational age and anthropometric measures at birth. Results: Maternal prenatal distress during late gestation was associated with significant reduction in birth weight (−217 g; p = .005), birth length (−1.2 cm; p = .005) and head circumference (−0.8 cm; p = .001). Prenatal stress was modestly but significantly associated with altered diurnal cortisol pattern (flattened cortisol decline and higher evening cortisol), which in turn was significantly related to reduced length of gestation. No evidence for a profound interaction between maternal cortisol level in late pregnancy and infant's anthropometric measures at birth (i.e., birth weight, length, head circumference) was found. Conclusion: Prenatal stress is associated with flattened circadian saliva cortisol profiles and reduced infant's anthropometric measures at birth. HPA system activity during pregnancy may be related to low gestational age. The effect of prenatal stress might be partly mediated by maternal-placental-fetal neuroendocrine mechanisms especially the dysregulation of diurnal cortisol profile.